INTEGRATING BUILDING INFORMATION MODELING AND VISUAL PROGRAMMING FOR BUILDING LIFE-CYCLE COST ANALYSIS - Likhitruangsilp, Veerasak; Le, Hang T. T.; Yabuki, Nobuyoshi; Ioannou, Photios G. (Proceedings of International Structural Engineering and Construction, 2019)
In recent years, the fierce competition in worldwide real-estate market has pushed the stakeholders towards the sustainability for buildings. Life-cycle cost (LCC) is an effective economic evaluation tool that provides a detailed account for all costs related to constructing, operating, maintaining, and disposing a construction project over a defined period of time. Awareness of better value of money throughout the LCC is beyond the initial price. Governments and Contracting authorities add the LCC as a key provision in the context of National Codes and Council Directives to promote the growth of sustainability concept. Current LCC analytical methods are costly, laborious, and time-consuming due to the difficulties of obtaining information and implementing many single LCC analyses for all building elements, which may be attributed to the inaccuracy of results. Building information modeling (BIM) is a modern technology that can potentially overcome the asperities that obstruct practical LCC implementation. This paper develops a new automated system for performing LCC analyses for new building projects by integrating BIM authoring programming with visual programming. The proposed system consists of two main modules. The BIM module is designed to retrieve 3D geometric and physical parameters of building element types. The life-cycle cost calculation module can perform automatic estimating and report results. This system provides an economic evaluation tool for the owner to manage the total life-cycle budget of their projects.